The velocity and absorption of sound near the critical point of stratification in the solution nitrobenzene–n-hexane - Bulavin, L. A.; Bilous О. I.; Svechnikova О. S. (Reports of the National Academy of Sciences of Ukraine, 2016)
The acoustic research of a binary solution nitrobenzene–n-hexane with various concentrations in a wide range of frequencies near its upper critical point of stratification is executed. It is shown that, by the dynamic scaling theory, the velocity of sound should be analyzed separately in three dynamic areas, where the role of fluctuations is absent, significant, or is on the verge of definition. Analysis of the temperature dependence of the velocity of ultrasound allowed us to estimate the lifetime of fluctuations of the concentration in the solution nitrobenzene–n-hexane at its approach to the critical point from the homogeneous state up to 0.1 K.